2003
DOI: 10.1021/jp036411u
|View full text |Cite
|
Sign up to set email alerts
|

Solution pKa Values of the Green Fluorescent Protein Chromophore from Hybrid Quantum-Classical Calculations

Abstract: We present a theoretical study of the four aqueous microscopic dissociation constants relating the relevant protonation forms (cation, neutral, anion, zwitterion) of the chromophore of the green fluorescent protein (GFP) in the ground and excited states. To take the protonation-state-dependent torsional flexibility around the ring-bridging bonds into account, configuration integrals in the torsion space were evaluated to yield the free energy differences. Conformational energies were calculated within a semie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
60
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(70 citation statements)
references
References 55 publications
7
60
1
Order By: Relevance
“…35 Upon electronic excitation, the pK a of the chromophore is reduced. 39,40 In the case of wtGFP the effect is to make the anionic I* form more stable. However, the proton transfer proceeds from A* to I* through a barrier, leading to the observed picosecond lifetime of the A* and its sensitivity to isotopic exchange.…”
Section: Discussionmentioning
confidence: 99%
“…35 Upon electronic excitation, the pK a of the chromophore is reduced. 39,40 In the case of wtGFP the effect is to make the anionic I* form more stable. However, the proton transfer proceeds from A* to I* through a barrier, leading to the observed picosecond lifetime of the A* and its sensitivity to isotopic exchange.…”
Section: Discussionmentioning
confidence: 99%
“…For the diabatic potential in the CTP simulations we chose a barrier of 4 kcal/mol around /, from the excited-state energy profile of / torsion reported in [17]. Another semiempirical calculation yields a larger value for the maximum at / = 90°(around 10 kcal/ mol [31]). We made some CTP trial runs using this value, and observed only small deviations from our results with the lower value.…”
Section: Methodsmentioning
confidence: 99%
“…21,[24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] Recently quantum chemical calculations, using thermodynamical parameters such as Gibbs free energy, have reported good correlations between calculated and experimental acidities of a wide range of organic and inorganic acids. 18,[42][43][44][45][46][47][48][49][50] For example, gas phase and solution phase acidities of some organic compounds investigated by Namazian et al and Kheirjou et al reported good correlation between ab initio calculations of pKa values with the experimental data. 19,21,[51][52] However, to the best of our knowledge, there is no data on pKa calculations of arsonic acids by quantum chemical methods, and experimentally determined pKa values are limited to a small group of arsonic acid derivatives.…”
Section: Introductionmentioning
confidence: 98%